Influence of crop rotation factor on the herbological state of crops of legumes and legumes - Vavrynovych, O.; Kachmar, O.; Dubitsky, O.; Dubitskaya, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The results of the study on the influence of the crop rotation factor on the potential and actual oblique crops of cereals and legumes are given. It was established that in the complex of measures for controlling the number of crop rotation weeds are of paramount importance, since individual crops can compete well with weeds.